Negotiating Learning:Are shortcuts good or bad for our students? - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
Today’s increasingly globalised world places specific demands on young people pursuing tertiary education. There is a growing contention that students are increasingly “engaging in shortcut behaviour” due to the competitive nature of studies at Malaysian universities.